PENALARAN USHUL FIQH IBNU HAZM (Analisis Penolakan Illat dan Qiyas Sebagai Dalil Hukum Islam) - Nur Khoirin YD (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
Ibn Hazm al Qurthubi is among the opponents of the use of illatand qiyas arguing that nash of al-Qur’an and Hadith can beapplied to any problems simply by understanding ma’na anddhahir of texts. Reasoning of musbit al-Qiyas (the proponents ofQiyas) that syari’a does not provide answer to all problems is afalse logic according to Ibn Hazm since this argument contradictsto al-Qur’an’s statement. Whoever uses qiyas as a legal reasoningis similar to believing that Qur’an is failed to provide guidance. Inthe process of legal reasoning, Ibn Hazm would refer to al-Qur’an,Hadith and Ijma’. Should those three sources do not provide theanswer, he used dalil by understading the hidden meaning of thetexts.